MENTAL HEALTH AND COVID-19 PANDEMIC - Marić Bojović, Nađa (Medicinski podmladak, 2021)
Mental health (MH) and illness reflect bio-psycho-social balance / imbalance and extend into multidimensional space. In the current pandemic, the entire area of MH / illness is at increased risk of contamination not only by infection, but also by many other aspects of this complex public health crisis. There are at least three mechanisms by which the COVID-19 pandemic can create new-onset mental conditions: 1) Psychological factor - increased degree of emotional suffering after extremely severe traumatic events or long-term life-threatening exposures); 2) Social factor - risks related to interaction with the environment: a) emotional deprivation; b) cognitive disintegration related to infodemia; and c) existential, primarily economic fears that destabilize relationships (within the family and beyond); 3) Biological factor - neuropsychiatric effects of the virus itself. In addition to the new-onset conditions (although in essence they are not completely "new", because they largely depend on individual dispositions), the pandemic also has an impact on people who already have a history of mental disorders.This review paper will present the most important information from relevant sources related to mental health and the COVID-19 pandemic related to the first year of exposure. Emphasis will be on research that has attracted attention with sample size and representativeness, as well as a reliable methodology, with the aim of not losing sight of the heterogeneity of the pandemic effects on mental health.
Keywords: COVID-19; Mental health; Psychiatry; Disorders; Pandemic; Psychosis